Decreased sensitivity to artesunate and chloroquine of Plasmodium falciparum infecting hemoglobin H and/or hemoglobin Constant Spring erythrocytes - Y. Yuthavong (2018)
Plasmodium falciparum infecting hemoglobin (Hb) H and/or Hb Constant Spring erythrocytes in vitro was relatively more resistant than that infecting normal erythrocytes to artesunate and chloroquine, while the sensitivity to pyrimethamine was unchanged. The 50% inhibitory concentrations (IC 50 ) for artesunate in HbH (α-thal 1/α-thal 2), HbH (α-thal 1/Hb Constant Spring), and homozygous Hb Constant Spring erythrocytes were 4.5 ± 2.8, 8.5 ± 3.2, and 2.6 ± 1.6 nM compared with 0.82 ± 0.35 nM in normal erythrocytes (P < 0.002 for all three cases). The IC 50 for chloroquine were 97 ± 46, 162 ± 67, and 93 ± 36 nM, respectively, in the variant erythrocytes, compared with 48 ± 13 nM in normal erythrocytes (P < 0.002, 0.002, and 0.02, respectively). The differences in sensitivity to artesunate and chloroquine of the parasite infecting HbH erythrocytes are probably related to their oxidative mode of action and relatively high amounts of antioxidant enzymes in the host erythrocytes. This novel example of dependence of the host of the malarial parasite drug sensitivity may have implications for chemotherapy of malaria in patients with genetically variant erythrocytes.